2007
DOI: 10.1111/j.1471-0528.2007.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

The burden of caesarean section refusal in a developing country setting

Abstract: Objective To investigate the prevalence, aetiology and outcomes of caesarean section refusal in pregnant women.Design A prospective controlled study.Setting University of Nigeria Teaching Hospital and Aghaeze Hospital, Enugu, Nigeria.Population A total of 62 Nigerian women who declined elective caesarean section.Method Interviewer-administered questionnaires at the time of caesarean section refusal and postdelivery. The delivery outcomes of the subjects were compared with that of a matched control group of wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
89
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 12 publications
11
89
3
Order By: Relevance
“…The fear is majorly as a result of death of a close relative during caesarean section, past unpleasant experiences in previous caesarean sections and unpleasant stories from other women. 8 Our study also shows that 82.0% refuse CS due to family preference to vaginal delivery. This negative acceptance may be due to ignorance and poor educational background.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…The fear is majorly as a result of death of a close relative during caesarean section, past unpleasant experiences in previous caesarean sections and unpleasant stories from other women. 8 Our study also shows that 82.0% refuse CS due to family preference to vaginal delivery. This negative acceptance may be due to ignorance and poor educational background.…”
Section: Discussionsupporting
confidence: 55%
“…This finding agrees with Chigbu and Iloabachie who stated that one of the reasons given by women for turning down caesarean section was the desire to experience vaginal delivery. 8 Myles also stated that they feel disappointed not to have experienced a normal delivery and they do not enjoy the accompanying sense of achievement. 3 The study revealed that knowledge and perception of pregnant women towards caesarean section is negative/low with 73% considering CS as dangerous and 63% unaware that a vaginal birth is still possible after CS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations